An independent endocytic pathway stimulates different monocyte subsets by the a2 N-terminus domain of vacuolar-ATPase - Kwong, Christina (Landes Bioscience, 2013)
The vacuolar ATPase (V-ATPase) plays an important role in tumor progression and metastases. A novel peptide from the a2 isoform of V-ATPase called a2NTD has been shown to exert an immunoregulatory role in the tumor microenvironment by controlling the maturation of monocytes toward a tumor-associated macrophage phenotype. Our data indicate that a2NTD binds to the surface of monocytes. a2NTD was preferentially endocytosed by pro-inflammatory monocytes bearing a CD14(++)CD16(+) phenotype, which is associated with the monocyte-to-macrophage maturation process. Both a2NTD binding and internalization led to production of the pro-inflammatory cytokines interleukin (IL)-1α and IL-1β by CD14(++)CD16(-) (classical) and CD14(++)CD16(+ )(intermediate) monocytes. a2NTD was internalized via a macropinocytosis mechanism utilizing scavenger receptors. However, the inhibition of a2NTD endocytosis did not reduce cytokine production by monocytes. This points to the existence of two receptors that respond to a2NTD: scavengers receptors that mediate cellular uptake and an hitherto unidentified receptor stimulating the production of inflammatory cytokines. Both of these monocyte receptors may be important in generating the localized inflammation that is often required to promote tumor growth and hence may constitute novel targets for the development of anticancer drugs.